Ferrite composition, electronic component, and power supply device

JP7643912B2Active Publication Date: 2025-03-11TDK CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021060970
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-03-11
Estimated Expiration
2041-03-31

AI Technical Summary

Benefits of technology

【0011】 一般的に、比較的磁路断面積が小さいコアの特性を元にして製品設計を行う。しかし、実際の製品は磁路断面積が大きい場合が多く、また、形状が複雑であり磁路断面積が均一ではないことが多い。このため製品設計段階の特性と実製品の特性とが一致しないことがある。これに対して、本発明に係るフェライト組成物は、上記の構成を有することで、コアの形状またはサイズの違いによる渦電流損失の変化を低減できる、すなわち、コアのサイズまたは形状の違いによる渦電流損失の変化を抑制できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643912000001
    Figure 0007643912000001
  • Figure 0007643912000002
    Figure 0007643912000002
  • Figure 0007643912000003
    Figure 0007643912000003
Patent Text Reader

Abstract

To provide: a ferrite composition capable of reducing the change of eddy current loss due to a difference in the size or shape of a core; an electronic component using the ferrite composition; and a power supply using the electronic component.SOLUTION: A ferrite composition has a main component and an accessory component. The main component is constituted of 51.0 to 53.5 mol% of iron oxide in terms of Fe2O3, 7 to 14 mol% of zinc oxide in terms of ZnO and the remainder consisting of manganese oxide; and the accessory component includes 0.09 to 0.27 pts.mass of cobalt in terms of CoO, 0.13 to 0.45 pts.mass of titanium in terms of TiO2, 0.06 to 0.25 pts.mass of calcium in terms of CaCO3 and 0.015 to 0.045 pts.mass of niobium in terms of Nb2O5 to 100 pts.mass of the main component.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ferrite composition, and an electronic component and a power supply device that include the ferrite composition. [Background technology]

[0002] In recent years, electronic devices have become smaller and more efficient, and there is a strong demand for smaller and more efficient electronic components used in power supplies, etc. To achieve this, low loss characteristics are required for the ferrite sintered bodies used in electronic components such as coils and transformers.

[0003] Generally, the magnetic core loss Pcv of a ferrite composition consists of hysteresis loss Phv, eddy current loss Pev, and residual loss Prv, and the eddy current loss Pev varies greatly depending on the size or shape of the core (magnetic core). Previous technology was unable to suppress the change in eddy current loss Pev caused by differences in core size or shape, and when a ferrite core was actually manufactured, it was often impossible to obtain the designed value.

[0004] In Patent Document 1, low loss is achieved at 300 kHz-100 mT, 100°C by adjusting the main components to reduce magnetic anisotropy and magnetostriction, adjusting the minor components to obtain sufficient electrical resistivity, and controlling the amount of unavoidable impurities.

[0005] Moreover, in Patent Document 2, the focus is on preventing thermal runaway in a transformer, and loss is reduced at temperatures of 120° C. or higher by simultaneously adding CoO and TiO2.

[0006] Furthermore, in Patent Document 3, a composition to which CoO and TiO2 are simultaneously added reduces loss at 100 to 300 kHz.

[0007] However, Patent Documents 1 to 3 do not consider changes in eddy current loss due to differences in core shape. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 6730545 [Patent Document 2] Patent No. 5786322 [Patent Document 3] JP 2004-35372 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made in consideration of the above-mentioned circumstances, and an object of the present invention is to provide a ferrite composition capable of reducing changes in eddy current loss due to differences in core size or shape, an electronic component using the ferrite composition, and a power supply device using the electronic component. [Means for solving the problem]

[0010] In order to achieve the above object, the ferrite composition according to the present invention comprises: Contains a main component and a subcomponent, The main component is composed of 51.0 to 53.5 mol % of iron oxide calculated as Fe2O3, 7 to 14 mol % of zinc oxide calculated as ZnO, and the remainder being manganese oxide, The auxiliary components include 0.09 to 0.27 parts by mass of cobalt calculated as CoO, 0.13 to 0.45 parts by mass of titanium calculated as TiO2, 0.06 to 0.25 parts by mass of calcium calculated as CaCO3, and 0.015 to 0.045 parts by mass of niobium calculated as Nb2O5, relative to 100 parts by mass of the main component.

[0011] Generally, product design is based on the characteristics of a core with a relatively small magnetic path cross-sectional area. However, actual products often have a large magnetic path cross-sectional area, and often have complex shapes and non-uniform magnetic path cross-sectional areas. For this reason, the characteristics at the product design stage may not match the characteristics of the actual product. In contrast, the ferrite composition according to the present invention has the above-mentioned configuration, and thus can reduce the change in eddy current loss due to differences in the shape or size of the core, i.e., can suppress the change in eddy current loss due to differences in the size or shape of the core.

[0012] The ferrite composition according to the present invention can be used as a magnetic core or a magnetic sheet (for non-contact power supply, electromagnetic wave absorber, noise filter, etc.) contained in various electronic components such as inductors, transformers, choke coils, reactors, antennas, coils for non-contact power supply, etc. In particular, the ferrite composition according to the present invention is preferably used as a magnetic core of a power supply transformer, and this power supply transformer can be incorporated into, for example, an on-vehicle switching power supply device used in an EV (Electric Vehicle), a PHV (Plug-in Hybrid Vehicle), or a commuter (vehicle), a power supply device for home or industrial electric equipment, or a power supply device for computer equipment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described in detail.

[0014] The ferrite composition according to the present embodiment may be in the form of a bulk such as a sintered body, a powder, or a thin film, and the form is not particularly limited. The ferrite composition according to the present embodiment has a main component and a subcomponent. The main component is composed of iron oxide, zinc oxide, and manganese oxide. On the other hand, the subcomponent includes at least cobalt (Co), titanium (Ti), calcium (Ca), and niobium (Nb).

[0015] First, the composition of the main components will be described. If the entire main components are taken as 100 mol%, the content of iron oxide is in the standard range of 51.0 to 53.5 mol%, and preferably 51.25 to 52.8 mol%, calculated as Fe2O3. The content of zinc oxide is in the standard range of 7 to 14 mol%, and preferably 8.6 to 12 mol%, calculated as ZnO. The content of manganese oxide is determined as the remainder of the main components by determining the content of iron oxide and the content of zinc oxide, which are the other main components.

[0016] The above-mentioned main component constitutes main component particles having a spinel-type crystal structure in the cross section of the ferrite composition. Here, the spinel-type crystal structure is expressed by the stoichiometric composition formula AB2O4, with Mn and Zn occupying the A site and Fe occupying the B site. In this embodiment, the main component particles having the spinel structure preferably have an average particle size of 6 to 18 μm, more preferably 8 to 14 μm, in terms of the circle equivalent diameter. The average particle size of the main component particles can be measured by observing the cross section of the ferrite composition with a SEM (scanning electron microscope) or a STEM (scanning transmission electron microscope), and performing image analysis of the obtained cross section photograph.

[0017] On the other hand, the contents of the subcomponents are expressed as a ratio to 100 parts by mass of the main component, that is, as the amount of the outer frame. In this embodiment, the reference range of the Co content is 0.09 to 0.27 parts by mass, preferably 0.13 to 0.27 parts by mass, and more preferably 0.21 to 0.27 parts by mass, calculated as CoO. The reference range of the Ti content is 0.13 to 0.45 parts by mass, preferably 0.13 to 0.35 parts by mass, and more preferably 0.13 to 0.225 parts by mass, calculated as TiO2. The reference range of the Ca content is 0.06 to 0.25 parts by mass, and more preferably 0.07 to 0.21 parts by mass, calculated as CaCO3. The reference range of the Nb content is 0.015 to 0.045 parts by mass, calculated as Nb2O5.

[0018] The form in which each of the minor components exists inside the ferrite composition is not particularly limited. For example, each of the minor components may be dissolved in the main component particles, or may exist as various compounds such as oxides, composite oxides, and carbonates at the grain boundaries of the main component particles.

[0019] More specifically, it is believed that Co and Ti are mainly dissolved in the main component particles, and part of the Fe in the spinel lattice is replaced by the dissolved Co or Ti. In particular, it is believed that by adding Co and Ti simultaneously, Fe in the B site of the spinel lattice is more likely to be replaced by Co or Ti, not in the A site. When Fe in the spinel lattice is replaced by Co or Ti, the temperature dependence of the magnetic anisotropy constant is reduced, and as a result, the temperature dependence of the magnetic loss is also reduced.

[0020] On the other hand, it is considered that Ca mainly exists as a compound at the grain boundaries of the main component particles and is dissolved in the vicinity of the grain boundaries of the main component particles. It is considered that the existence of Ca in the above form improves the sinterability of the ferrite composition and increases the grain boundary resistance. In addition, Nb is considered to contribute to the uniformity of the crystal structure of the ferrite composition.

[0021] In addition, the ferrite composition of this embodiment preferably does not substantially contain Zr. In this embodiment, "substantially does not contain Zr" means that the content of Zr is 0.009 parts by mass or less in terms of ZrO2 with respect to 100 parts by mass of the main component. The content of Zr is more preferably 0 to less than 0.005 parts by mass.

[0022] In addition to the above-mentioned minor components, the ferrite composition of the present embodiment may contain other minor components such as Si, V, and P, and unavoidable impurities. The content of the other minor components and unavoidable impurities is an amount that does not interfere with the suppression of Pev change. For example, the total content of the unavoidable impurities is preferably about 0 to 0.001 parts by mass relative to 100 parts by mass of the main component. In addition, it is preferable to select Si and / or V as the other minor components. In this case, the content of Si is preferably 0.005 to 0.02 parts by mass in terms of SiO2, and the content of V is preferably 0.005 to 0.04 parts by mass in terms of V2O5, relative to 100 parts by mass of the main component. Si is considered to contribute to improving the sinterability of the ferrite composition. In addition, V is considered to exist mainly as a compound at the grain boundary of the main component particles, and is considered to work to increase the grain boundary resistance.

[0023] The content of the main component and the content of the subcomponent as described above can be measured by component analysis using an X-ray fluorescence analyzer (XRF). In addition, they may be measured by component analysis using an electron probe microanalyzer (EPMA) during cross-sectional observation using a SEM or STEM, or they can be measured using X-ray diffraction (XRD).

[0024] Next, an example of a method for producing the ferrite composition according to the present embodiment will be described.

[0025] First, the starting materials of the main components are prepared and weighed so as to have a predetermined composition after firing. As the starting materials of the main components, oxide powders or powders of compounds that become oxides by heating (such as carbonate powders) can be used, and specifically, α-Fe2O3 powder, Mn3O4 powder, and ZnO powder are preferably used. In addition, powders of composite oxides containing two or more metals may be used as the starting materials of the main components. For example, a composite oxide powder containing Fe and Mn is obtained by oxidizing and roasting an aqueous solution containing iron chloride and manganese chloride. Then, ZnO powder may be added to and mixed with this composite oxide powder to obtain the raw material of the main components. The average particle size of each of the starting materials described above is preferably 0.1 to 3.0 μm.

[0026] Next, the weighed starting materials of the main components are mixed in a mixer such as a ball mill, and then calcined. In this case, the mixing may be wet or dry, and if wet mixing is selected, the mixture is appropriately dried after mixing and then calcined. The conditions of the calcination treatment are preferably a holding temperature of 800 to 1100°C and a temperature holding time (temperature stabilization time) of 0.5 to 5 hours. The calcined material obtained by calcination under such conditions is pulverized using various pulverizers until the average particle size becomes about 0.5 to 3.0 μm. When a powder of a composite oxide containing Fe and Mn is used as the starting material of the main components, the calcination treatment may be omitted.

[0027] Next, the starting materials of the subcomponents are added to the raw materials after calcination and mixed. As the starting materials of the subcomponents, oxide powders or powders of compounds that become oxides by heating can be used, as in the case of the main component. Specifically, CoO powder, TiO2 powder, CaCO3 powder, and Nb2O5 powder can be used. The average particle size of the starting materials of the subcomponents is also preferably 0.1 to 3.0 μm. The starting materials of the subcomponents may be added after the calcination process, and then the above-mentioned pulverization process is performed, so that the calcined material is pulverized while mixing the main component and the subcomponents. The starting materials of the subcomponents may be added after the calcination process and mixed. Furthermore, the CoO powder and TiO2 powder may be mixed in advance with the starting materials of the main component and then subjected to the calcination process.

[0028] Next, a suitable binder such as polyvinyl alcohol is added to the mixed powder of the main component and the subcomponent obtained above and kneaded to obtain a composite material. This composite material is then molded into a predetermined shape by a method such as injection molding or mechanical press molding to obtain a molded body. For example, in injection molding, the composite material is made into a slurry and poured into a mold to obtain a molded body. In mechanical press molding, a granular composite material is filled into a mold and pressurized to obtain a molded body.

[0029] Next, the molded body obtained above is fired. The firing conditions are a holding temperature of 1150°C to 1400°C, more preferably 1200°C to 1300°C, and a temperature holding time of 1 to 10 hours, more preferably 2 to 6 hours. In addition, in the temperature rise process from the start of heating to the holding temperature, the temperature rise rate is preferably 50 to 300°C / hour, and in the temperature drop process from the holding temperature to 900°C, the cooling rate is preferably 50 to 200°C / hour. In addition, the atmosphere during firing is a mixed atmosphere of oxygen and nitrogen, and the oxygen partial pressure in the temperature rise process and temperature holding process is preferably 0.1 to 5.0 vol%. In addition, in the temperature drop process from the holding temperature to 1000°C, the oxygen partial pressure is gradually reduced, and at 1000°C or less, the oxygen partial pressure is preferably 0.02 vol% or less.

[0030] By firing under the above conditions, a ferrite composition as a sintered body can be obtained. The ferrite composition as a sintered body according to the present embodiment can be used as a magnetic core or a magnetic sheet in various electronic components.

[0031] When the ferrite composition according to this embodiment is used as a magnetic core, the shape may be E-shaped, F-shaped, I-shaped, T-shaped, U-shaped, drum-shaped, toroidal, pot-shaped, cup-shaped, or simply plate-shaped or rectangular prism-shaped.

[0032] The sintered body obtained after firing may be pulverized to obtain a powdered ferrite composition. In this case, a binder or a solvent may be added to the obtained sintered body powder to form a paste. The paste is then formed into a sheet by a sheet method or an extrusion method, and then appropriately dried or heat-treated to obtain a thin-film ferrite composition. Such a thin-film ferrite composition can be used, for example, as a magnetic core for a thin-film inductor, or as a magnetic sheet for an antenna or non-contact power supply (for non-contact power supply, electromagnetic wave absorber, noise filter).

[0033] The magnetic core loss Pcv of a ferrite composition is composed of hysteresis loss Phv, eddy current loss Pev, and residual loss Prv, and the conventional eddy current loss Pev varies greatly depending on the size or shape of the core. Specifically, the larger the core size, the greater the eddy current loss tends to be, and in particular, the larger the magnetic path cross-sectional area of ​​the core, the greater the eddy current loss tends to be.

[0034] In contrast, since the ferrite composition according to the present embodiment has the contents of the main and sub-components within predetermined ranges, it is possible to suppress changes in eddy current loss due to differences in the size or shape of the core (magnetic core).

[0035] Therefore, the size and shape of the ferrite composition according to this embodiment are not particularly limited.

[0036] As described above, the ferrite composition of the present embodiment is suitable as a magnetic core material or a magnetic sheet, and can be used in electronic components such as transformers, inductors, choke coils, reactors, antennas, and coils for non-contact power supply. Among the above electronic components, the ferrite composition is particularly suitable for use as a transformer. The transformer containing the ferrite composition of the present embodiment is particularly preferably incorporated into a power supply device. Examples of the power supply device include a switching power supply device in which the above transformer is combined with an input filter, a switching circuit, a rectifier circuit, a smoothing circuit, and the like.

[0037] Although the embodiment of the present invention has been described above, the present invention is not limited to the above-mentioned embodiment, and various modifications can be made within the scope of the present invention. EXAMPLES

[0038] The present invention will be described in more detail below using examples and comparative examples, although the present invention is not limited to the following examples.

[0039] In this experiment, ferrite cores of Examples 1 to 41 and Comparative Examples 1 to 20 having the compositions shown in Tables 1 to 5 were produced and their eddy current losses Pev were measured. The ferrite cores of each Example and Comparative Example were produced by the following procedure.

[0040] First, α-Fe2O3 powder, Mn3O4 powder, and ZnO powder were prepared as starting materials for the main components, and were weighed out so that the ratios would be the specified ratios after firing. The weighed powders were then wet-mixed in a ball mill to obtain a raw material mixture. After drying the raw material mixture, it was pre-fired at 900°C for 3 hours in an air atmosphere to obtain a pre-fired material.

[0041] Next, the calcined material was put into a ball mill filled with steel balls and pulverized for 16 hours to obtain a pulverized powder with an average particle size of 1 to 2 μm. The pulverized powder was then wet-mixed with the starting materials for the subcomponents and then dried to obtain a mixed powder. At this time, CoO powder, TiO2 powder, CaCO3 powder, and Nb2O5 powder were prepared as starting materials for the subcomponents and weighed to have a predetermined ratio after sintering. In addition, in each example and each comparative example, SiO2 powder and V2O5 powder were also added in a predetermined amount as subcomponents in addition to the above.

[0042] Next, 0.8 parts by mass of polyvinyl alcohol was added to 100 parts by mass of the mixed powder, which was then sprayed and dried using a spray dryer to produce granules. The resulting granules were then filled into two types of molds and molded under a pressure of 100 MPa to obtain a toroidal shaped compact.

[0043] Here, the "two types of molds" refer to a mold for obtaining a smaller "small core" and a mold for obtaining a larger "large core." That is, by the above process, a "small molded body" that becomes the "small core" after firing and a "large molded body" that becomes the "large core" after firing were obtained.

[0044] Next, the above compacts ("small compact" and "large compact") were fired under the following conditions. The firing conditions were a holding temperature of 1250°C, a holding time of 5 hours, and a firing atmosphere of a mixture of oxygen and nitrogen. The oxygen partial pressure during the temperature holding process was 4 vol%, and during the temperature drop process, the oxygen partial pressure was monotonically decreased in the temperature range of 1250°C to 1000°C, and was controlled to be 0.02 vol% in the temperature range of 1000°C or less. The heating rate was 200°C / hour, and the cooling rate was 100°C / hour. By firing under these conditions, ferrite cores ("large core" and "small core") were obtained as sintered bodies.

[0045] The shape of the obtained ferrite core was a toroidal shape in both the small core and the large core as described above. The dimensions of the produced small core and large core were as follows: Small core: Outer diameter: 20 mm, inner diameter: 10 mm, height: 5 mm, magnetic path cross-sectional area: 25 mm 2 Large core: Outer diameter: 50mm, inner diameter: 10mm, height: 10mm, magnetic path cross-sectional area: 200mm 2

[0046] The composition of the produced ferrite core was analyzed by XRF. The measurement results are shown in Tables 1 to 5.

[0047] In addition, for each small core and each large core of each Example and Comparative Example, the magnetic loss Pcv was measured at 100° C. under the conditions of frequencies of 200 kHz, 300 kHz, and 400 kHz and a magnetic flux density of 100 mT. The eddy current loss Pev was calculated by the following method. As shown in formula (1), the magnetic loss Pcv at frequencies between 200 kHz and 400 kHz can be expressed as the sum of the hysteresis loss Phv and the eddy current loss Pev. Pcv = Phv + Pev (1) Next, hysteresis loss Phv is proportional to frequency f, and Pev is proportional to the square of f, so it can be expressed as shown in equation (2). Pcv = Kh x f + Ke x f 2 (2) Here, Kh is the hysteresis loss coefficient and Ke is the eddy current loss coefficient. By dividing both sides of equation (2) by frequency f, we can express it as equation (3). Pcv / f = Kh + Ke × f (3) From equation (3), Pcv / f is a linear function of frequency f, so the eddy current loss coefficient Ke can be obtained from the slope. That is, the eddy current loss coefficient Ke was obtained based on the magnetic loss Pcv at frequencies of 200 kHz, 300 kHz, and 400 kHz. Based on the obtained eddy current loss coefficient Ke, the eddy current loss Pev was calculated by the following formula (4). Pev = Ke x f 2 (4)

[0048] Furthermore, ΔPev was calculated by the following formula (5) based on the Pev of each small core and each large core of each Example and Comparative Example. The results are shown in Tables 1 to 5. Note that when ΔPev was 400 kW / m 3 The following conditions were judged to be good: ΔPev = (Pev of large core) - (Pev of small core) (5)

[0049] [Table 1]

[0050] Table 1 mainly shows the results of experiments in which the contents of the minor components were fixed and the composition of the major components was changed.

[0051] As shown in Table 1, when the main components are composed of 51.0 to 53.5 mol % iron oxide calculated as Fe2O3, 7 to 14 mol % zinc oxide calculated as ZnO, and the remainder manganese oxide, and when a predetermined amount of a subcomponent is contained (Examples 1 to 9), ΔPev is 400 kW / 3 or less, and it was confirmed that ΔPev was smaller than those in Comparative Examples 1 to 4.

[0052] [Table 2]

[0053] [Table 3]

[0054] Tables 2 and 3 show the experimental results when the contents of the secondary components Co and Ti were changed in a case where the main components were 52.6 mol % iron oxide calculated as Fe2O3, 9.5 mol % zinc oxide calculated as ZnO, and the remainder manganese oxide.

[0055] As shown in Tables 2 and 3, when cobalt is contained in an amount of 0.09 to 0.27 parts by mass in terms of CoO and titanium is contained in an amount of 0.13 to 0.45 parts by mass in terms of TiO as the auxiliary components (Examples 10 to 22), ΔPev is 400 kW / m 3 or less, and it was confirmed that ΔPev was smaller than those of Comparative Examples 5 to 12.

[0056] [Table 4]

[0057] Table 4 shows the experimental results when the contents of the secondary components Co and Ti were changed in a case where the main components were 52.2 mol % iron oxide calculated as Fe2O3, 11.5 mol % zinc oxide calculated as ZnO, and the remainder manganese oxide.

[0058] As shown in Table 4, when cobalt is contained in an amount of 0.09 to 0.27 parts by mass in terms of CoO and titanium is contained in an amount of 0.13 to 0.45 parts by mass in terms of TiO as the auxiliary components (Examples 23 to 29), ΔPev is 400 kW / m 3 The following was confirmed.

[0059] [Table 5]

[0060] Table 5 shows the experimental results when the contents of the auxiliary components Ca and Nb were changed.

[0061] As shown in Table 5, when calcium is contained in an amount of 0.06 to 0.25 parts by mass in terms of CaCO3 and niobium is contained in an amount of 0.015 to 0.045 parts by mass in terms of Nb2O5 as the auxiliary components (Examples 30 to 41), ΔPev is 400 kW / m 3 The following was confirmed.

[0062] Taking the results of Tables 1 to 5 together, it was confirmed that the change in eddy current loss due to differences in core size or shape can be suppressed by making the composition of the main components and the contents of each of the subcomponents (Co, Ti, Ca, Nb) all satisfy the standard range of the present invention. It was also confirmed that if even one of the main components and subcomponents does not satisfy the standard range, the change in eddy current loss due to differences in core size or shape increases.

Claims

1. A ferrite composition having a main component and a subcomponent, The main component is Fe. 2 O 3 % of iron oxide calculated as 51.25 to 52.8 mol % of zinc oxide calculated as ZnO, and the remainder being manganese oxide, The auxiliary components are 0.09 to 0.27 parts by mass of cobalt in terms of CoO and 0.09 to 0.27 parts by mass of titanium in terms of TiO relative to 100 parts by mass of the main component. 2 0.13 to 0.45 parts by mass of calcium in terms of CaCO 3 0.06 to 0.25 parts by mass of niobium in terms of Nb 2 O 5 The ferrite composition contains 0.015 to 0.045 parts by mass in terms of the amount of the ferrite.

2. An electronic component comprising a sintered body made of the ferrite composition according to claim 1.

3. A power supply device comprising the electronic component according to claim 2.

Citation Information

Patent Citations

  • Wide-temperature low-loss MnZn ferrite material and preparation method thereof

    CN102219487A

  • Endoscope apparatus

    JP1982086322A

  • Low loss ferrite material

    JP2004035372A

  • Ferrite sintered compact and method for producing the same

    JP2009227554A

  • Ferrite core

    JP2012116700A